Symmetrical Cutaneous Siderosis of the Upper Limbs - Elisa Zavattaro; Federica Veronese; Pamela Farinelli; Paola Savoia (Dr. Annil Mahajan, 2023)
Cutaneous Siderosis is a condition characterized by the hyperpigmentation of the soft tissues resulting from iron leakage occurring during iron replacement therapy. Even if it is a well-known condition, to date only a few reports are available in the literature, mainly describing it as a single lesion developing after intramuscular ferric injection, thus affecting the gluteal region. We report here a case of a 72-year-old patient that developed multiple macules affecting his upper limbs, after repeated intravenous iron extravasations. To our knowledge, this is the first report of Cutaneous Siderosis affecting symmetrically both the upper limbs with numerous elements.